"Tell them you smoke, you'll get more breaks": a qualitative study of occupational and social contexts of young adult smoking in Scotland. Issue 12 (31st December 2018) - Delaney, Hannah; MacGregor, Andrew; Amos, Amanda
Abstract : Objective: To explore young adults' perceptions and experiences of smoking and their smoking trajectories in the context of their social and occupational histories and transitions, in a country with advanced tobacco control. Design: Indepth qualitative interviews using day and life grids to explore participants' smoking behaviour and trajectories in relation to their educational, occupational and social histories and transitions. Setting: Scotland. Participants: Fifteen ever-smokers aged 20–24 years old in 2016–2017. Results: Participants had varied and complex educational/employment histories. Becoming and/or remaining a smoker was often related to social context and educational/occupational transitions. In several contexts smoking and becoming a smoker had perceived benefits. These included getting work breaks and dealing with stress and boredom, which were common in the low-paid, unskilled jobs undertaken by participants. In some social contexts smoking was used as a marker of time out and sociability. Conclusions: The findings indicate that while increased tobacco control, including smokefree policies, and social disapproval of smoking discourage smoking uptake and increase motivations to quit among young adults, in some social and occupational contexts smoking still has perceived benefits. This finding helps explain why smoking uptake continues into the mid-20s. It also highlights the importance of policies that reduce the perceived desirability of smoking and that create more positive working environments for young adults which address the types of working hours and conditions that may encourage smoking.